2017
DOI: 10.1002/hed.24704
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor regression by intratumoral STING agonists combined with anti–programmed death‐L1 blocking antibody in a preclinical squamous cell carcinoma model

Abstract: This study demonstrates the antitumor effects of CDNs in a HNSCC cell line. These preclinical data strongly support the future clinical development of intratumoral CDN in patients with HNSCC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1086-1094, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…injection into B16.F10 tumors was enhanced when combined with anti-programmed death-1 (PD-1) and anti-cytotoxic T-lymphocyte associated-4 (CTLA-4) antibodies ( 55 ). In other studies, CDNs together with anti-PD-1 incited much stronger antitumor effects than monotherapy in a mouse model of squamous cell carcinoma model as well of melanoma ( 59 , 60 ). Luo et al showed great synergy by combining a STING-activating nanovaccine and an anti-PD1 antibody, and suggested generation of long-term antitumor memory in TC-1 tumor model ( 61 ).…”
Section: Preclinical Evaluation Of Sting Agonists For Cancer Treatmenmentioning
confidence: 84%
“…injection into B16.F10 tumors was enhanced when combined with anti-programmed death-1 (PD-1) and anti-cytotoxic T-lymphocyte associated-4 (CTLA-4) antibodies ( 55 ). In other studies, CDNs together with anti-PD-1 incited much stronger antitumor effects than monotherapy in a mouse model of squamous cell carcinoma model as well of melanoma ( 59 , 60 ). Luo et al showed great synergy by combining a STING-activating nanovaccine and an anti-PD1 antibody, and suggested generation of long-term antitumor memory in TC-1 tumor model ( 61 ).…”
Section: Preclinical Evaluation Of Sting Agonists For Cancer Treatmenmentioning
confidence: 84%
“…Indeed, the synergistic combination of RR-CDG (i.t., every 3 days) with a PD-L1 blockade (i.p.,100 μg) stimulated stronger antitumor responses than monotherapy in a head and neck squamous cell cancer (HNSCC) mouse model [149]. Intramuscular (i.m.)…”
Section: Indirect Sting Agonistsmentioning
confidence: 99%
“…Moreover, a synergistic effect was seen when ADUS100 was combined with an anti-PD-1 antibody and an OX-40 agonist antibody where tumor clearance was seen in 40% of the mice compared to only 10% of the mice with ADUS100 treatment ( 128 ). STING agonists also showed increased tumor regression when combined with anti-PD1 antibody in a pre-clinical squamous cell carcinoma model ( 129 ). Based on the success in pre-clinical models, multiple clinical trials are ongoing to test STING agonist monotherapy or in combination with anti-PD1 antibodies (NCT03010176, NCT03172936).…”
Section: Targeting Type I Ifn Signaling Pathway As a Promising Stratementioning
confidence: 99%